2021
DOI: 10.18502/kss.v4i15.8232
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Evaluation on the Use of Learning Media During Pandemic

Abstract: This research aims to find out student assessments of the learning media used during the Covid-19 pandemic. We tested several learning media used, first is the WhatsApp group, zoom, and Learning Management System (LMS) used by campus. Descriptive statistic from 616 people (24.28% were male), we found that the use of text-based synchronus learning media was more desirable than the use of existing video or LMS. Positive ratings are mainly on the frequent use, effectiveness, flexibility, spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This research had been able to answer the problems found in previous studies. The limitations of Mutawa (2017), Mantara et al (2021), and Habib and Ramzan (2020) [11,15,16] had been answered through this research by showing that there were aspects of Discrepancy evaluation were used as a reference for evaluating the blended learning implementation at IT vocational schools in Bali. Limitations of Lippe and Carter (2018), Martín-Martínez et al (2020), Naibaho (2021) [12,14,17] had been answered through this research by showing the TOPSIS calculation process in determining the dominant aspects that must be improved.…”
Section: Indicatorsmentioning
confidence: 97%
See 1 more Smart Citation
“…This research had been able to answer the problems found in previous studies. The limitations of Mutawa (2017), Mantara et al (2021), and Habib and Ramzan (2020) [11,15,16] had been answered through this research by showing that there were aspects of Discrepancy evaluation were used as a reference for evaluating the blended learning implementation at IT vocational schools in Bali. Limitations of Lippe and Carter (2018), Martín-Martínez et al (2020), Naibaho (2021) [12,14,17] had been answered through this research by showing the TOPSIS calculation process in determining the dominant aspects that must be improved.…”
Section: Indicatorsmentioning
confidence: 97%
“…The limitation of Martín-Martínez et al's research was that it had not shown the dominant aspect that becomes improvement priority. The research was conducted by Mantara et al (2020) [15] showed evaluation activities toward learning media used in online learning during the Covid-19 pandemic. The limitation of Mantara et al's research was it had not shown the educational evaluation model used in evaluating the learning media in online learning.…”
mentioning
confidence: 99%